2020
DOI: 10.1038/s41598-020-71393-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes illuminate the evolutionary history of the Western honey bee (Apis mellifera)

Abstract: Western honey bees ( Apis mellifera ) are one of the most important pollinators of agricultural crops and wild plants. Despite the growth in the availability of sequence data for honey bees, the phylogeny of the species remains a subject of controversy. Most notably, the geographic origin of honey bees is uncertain, as are the relationships among its constituent lineages and subspecies. We aim to infer the evolutionary and biogeographical history of the honey bee from mitochondrial genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 94 publications
5
41
0
Order By: Relevance
“…Classification and geographical distribution of Ethiopian honey bees have been intensively discussed within the research community but methodological variations have been leading into contrasting results and opinions. While some recently published articles based on mitochondrial DNA analysis described the Ethiopian honey bees, with their evolutionary lineage Y, to be genetically distinct from other A. mellifera subspecies in neighbouring geographic areas (Boardman et al 2020;Franck et al 2001;Tihelka et al 2020), Hailu et al (2020) reported of maternal lineage O to be present in northern Ethiopia. Morphometric analysis investigating present subspecies was also not in agreement with each other (Amssalu et al 2004;Hailu et al 2021;Meixner et al 2011;Nuru et al 2002a;Radloff and Hepburn 1997;Ruttner 1988).…”
Section: Beekeeping In Ethiopiamentioning
confidence: 99%
“…Classification and geographical distribution of Ethiopian honey bees have been intensively discussed within the research community but methodological variations have been leading into contrasting results and opinions. While some recently published articles based on mitochondrial DNA analysis described the Ethiopian honey bees, with their evolutionary lineage Y, to be genetically distinct from other A. mellifera subspecies in neighbouring geographic areas (Boardman et al 2020;Franck et al 2001;Tihelka et al 2020), Hailu et al (2020) reported of maternal lineage O to be present in northern Ethiopia. Morphometric analysis investigating present subspecies was also not in agreement with each other (Amssalu et al 2004;Hailu et al 2021;Meixner et al 2011;Nuru et al 2002a;Radloff and Hepburn 1997;Ruttner 1988).…”
Section: Beekeeping In Ethiopiamentioning
confidence: 99%
“…The global diversity of A. mellifera is well recognised, as the honey bee has been the subject of numerous population genetic surveys using maternal and biparental genetic markers [13][14][15][16][17][18], along with morphometry [19][20][21][22][23]. These studies reveal high diversification within the species, with approximately 30 described subspecies grouped into five major evolutionary lineages: A (African), C (subspecies from east and south of the Alps), M (subspecies ranging from western and northern Europe to central Asia in the east), O (Oriental, subspecies from the Middle East), Y (subspecies from Arabian Peninsula and Ethiopia) [15,17,22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…About 30 A. mellifera subspecies have been described thus far, starting from morphometrical differences that are summarized by several classical studies in this field [ 21 , 22 , 23 , 24 , 25 ], and then complemented by investigations on the mitochondrial DNA (mtDNA) and nuclear genome variability [ 26 , 27 , 28 , 29 , 30 , 31 ]. These subspecies have been grouped into five major evolutionary lineages (A, C, M, O and Y), the following three of which are considered to be originally present in different European regions [ 25 ]: A, the African lineage, which was mainly spread through Southern Europe (Iberian peninsula, the close Gascony in Southwest France, and several Mediterranean islands, including Sicily); C, widespread in the east of Europe and in the Italian peninsula; M, which generally covers the northern part of Western Eurasia, from the British Isles through most of continental Europe, to the Ural and some areas in Central Asia.…”
Section: Introductionmentioning
confidence: 99%